Active compounds of Citrus hystrix DC in special cuisine of the Samawa Tribe, West Nusa Tenggara - Aliefman Hakim; Saprizal Hadisaputra; L. Rudyat Telly Savalas; Jono Irawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
The people of Sumbawa are famous for their various typical Sumbawa dishes. Typical dishes popular among the people and widely known in NTB are sepat and salty chili dishes. This dish is inseparable from flavoring Monte Sumbawa. Additional types of food, such as anointing, are also indispensable for Monte Sumbawa. Monte Sumbawa is a type of kaffir lime Citrus hystrix DC that grows in the Sumbawa area. Consumptionmonte sumbawa is very high in all areas of Sumbawa. This research aims to meet the community's needs and not depend on the fruiting season—innovation in essential oil distillation and packaging monte sumbawa in packaged products. The research method uses laboratory experiments. The content of active compounds was obtained using the GC-MS method. Based on the results of the GC-MS test, the active compound contains the major compound, linalool, with a weight percentage of 57.8%. Oil contains minor compounds such as 1-Octadecene (CAS).alpha.-Octadecene, 3-Cyclohexen-1-ol, 4-methyl-1-(1-methylethyl)- (4)-Ter , TRANS( .BETA.)-CARYOPHYLLENE, and GERMACRENE-D. Active compounds play an active role in supporting the health of the human body and as a detox against various cancer-causing free radicals. The product is packaged in a dropper bottle which is easy to use and can be stored for a long time. Society can use Monte anytime and no longer depend on the fruiting season.